Three new peculiar species of the genus Miltochrista Hübner, [1819] from China (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Huang, Si-Yao (Zootaxa, 2021)
Three new species of the genus Miltochrista are described from southwestern China: Miltochrista xihe Volynkin & Huang, sp. n., Miltochrista dongi Huang & Volynkin, sp. n. and Miltochrista huashen Volynkin & Huang, sp. n. Adults, male and female genitalia are illustrated.